Algorithm 819: AIZ, BIZ two Fortran 77 routines for the computation of complex Airy functions. - Gil, Amparo (ACM transactions on mathematical software.)
Two Fortran 77 routines for the evaluation of Airy functions of complex arguments Ai(z), Bi(z) and their first derivatives are presented. The routines are based on the use of Gaussian quadrature, Maclaurin series and asymptotic expansions. Comparison with a previous code by D. E. Amos [1986] is provided.